Effects of additional gonadotropin-releasing hormone and prostaglandin F2α treatment to an estradiol/progesterone-based embryo transfer protocol for recipient lactating dairy cows - Pereira, M. H.C. [UNESP]; Cappellozza, B. I.; Cerri, R. L.A.; Sanches, C. P. [UNESP]; Guida, T. G. [UNESP]; Barbosa, L. F.S.P. [UNESP]; Santos, J. E.P.; Vasconcelos, J. L.M. [UNESP] (American Dairy Science Association, 2023)
This study was designed to evaluate whether the utilization of a second PGF2α treatment at the end of an estradiol/progesterone (E2/P4)-based protocol with or without GnRH at the beginning of the protocol would improve pregnancy rates of lactating Holstein cows assigned to timed embryo transfer. A total of 501 lactating Holstein cows in 5 farms were enrolled in the experiment. Within farm, cows were blocked by parity and, within block, were assigned randomly to (1) insertion of an intravaginal P4 device (controlled internal drug-releasing device; CIDR) and estradiol benzoate on d −11, PGF2α on d −4, CIDR withdrawal and an injection of estradiol cypionate on d −2, and timed embryo transfer on d 7 (1-PGF; n = 164); (2) the same treatments as 1-PGF, but with PGF2α administered on d −4 and −2 (2-PGF; n = 171); and (3) 2-PGF with the addition of a GnRH treatment on d −11 (GnRH+2-PGF; n = 166). Ovaries were scanned by transrectal ultrasonography on d −11, −4, and 7, and blood samples were collected on d −11, −4, 0, and 7 for P4 determination. Treatment comparisons were performed using contrasts. The proportion of cows with a new corpus luteum on d −4 was greater in GnRH+2-PGF cows. Cows in 1-PGF had a greater P4 concentration on d 0 but lesser P4 on d 7 compared with cows in the other groups. Cows assigned to receive 2-PGF (2-PGF and GnRH+2-PGF) had greater estrus expression, and a greater proportion of cows ovulated to estradiol cypionate. No further contrast effects were observed for follicle diameter, double ovulation rate, pregnancy per embryo transfer (P/ET) on d 32 and 60, or pregnancy loss. As P4 concentration on d −4 increased, P/ET on d 60 tended to increase. Cows with P4 ≥3.66 ng/mL on d −4 had greater P/ET on d 32 and 60 than those with P4 below that threshold. Regardless of treatment, cows with P4 concentration ≥3.66 ng/mL also had a greater pregnancy per synchronized protocol (P/SP) on d 60. Also, a P4 concentration on d −4 (low or high) × follicle diameter (continuous) interaction tendency was observed when evaluating P/ET. Although P/ET did not differ among cows with different follicles sizes with reduced P4 concentration on d −4 (<3.66 ng/mL), it increased in cows with larger follicles exposed to increased P4 concentration (≥3.66 ng/mL). When P4 on d 0 was evaluated, P/ET on d 32 and 60 was greater for cows with low (≤0.09 ng/mL) versus high (>0.21 ng/mL) P4; as P4 concentration on d 0 increased, P/ET linearly decreased. In summary, cows with increased P4 concentrations during growth of the ovulatory follicular wave had improved P/ET. Administering a second PGF2α dose reduced P4 concentration on d 0 and increased ovulatory response to the protocol, but no benefits were observed on P/ET or P/SP.
Keywords: embryo transfer; gonadotropin-releasing hormone; progesterone; prostaglandin